2019
DOI: 10.1007/s00431-019-03362-3
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of diagnostic accuracy of screening tests ALT and ultrasound for pediatric non-alcoholic fatty liver disease

Abstract: Alanine aminotransferase (ALT) and ultrasound (US) are the most commonly used tools for detecting non-alcoholic fatty liver disease (NAFLD). No direct comparison of these two modalities in children exists. We aimed to compare head-to-head the diagnostic accuracy of ALT and US and their combination for detecting NAFLD in children with obesity. Ninety-nine children with severe obesity underwent simultaneous serum-ALT and abdominal ultrasound (US steatosis score 0–3). Proton magnetic resonance spectroscopy was us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
46
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(46 citation statements)
references
References 33 publications
0
46
0
Order By: Relevance
“…In addition, the majority of studies in children with biopsy-proven or MRI-diagnosed HS report that ALT levels and ultrasound techniques only show moderate diagnostic accuracy in terms of detecting HS in children, and that combining them leads to no improvement in sensitivity. 48,49 Other authors propose blood ALT concentrations of >35 IU/L as indicative of HS. However, while this cut-off has a high specificity (between 92% and 94%) it has only low sensitivity (between 24% and 48%).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the majority of studies in children with biopsy-proven or MRI-diagnosed HS report that ALT levels and ultrasound techniques only show moderate diagnostic accuracy in terms of detecting HS in children, and that combining them leads to no improvement in sensitivity. 48,49 Other authors propose blood ALT concentrations of >35 IU/L as indicative of HS. However, while this cut-off has a high specificity (between 92% and 94%) it has only low sensitivity (between 24% and 48%).…”
Section: Discussionmentioning
confidence: 99%
“…Among them, especially ALT, is a sensitive biomarker as an indicator associated with NAFLD [49]. In many clinical studies on NAFLD, an increased level of ALT has been considered as an independent predictor [50]. It is also generally accepted that GGT, which is an enzyme abundant in the liver, is elevated as a result of obesity and liver damage, and thus regarded as one of the predictors of liver mortality [51].…”
Section: Discussionmentioning
confidence: 99%
“…However, in children it has low sensitivity and specificity, and based on the available evidence, a 2014 systematic review concluded that the use of ultrasound for NAFLD diagnosis or grading in youth is not recommended 89 . In a study of children with obesity, with MRI as the reference ‘gold standard’ method, ALT and ultrasound sensitivity performed similarly in detecting NAFLD cases (44% vs 51%, respectively) and the concomitant use of both methods for screening didn't improve the diagnostic accuracy to detect NAFLD 90 …”
Section: Screeningmentioning
confidence: 99%